Computer and experimental analyses of the stress state in the cement hip joint endoprosthesis body - Tabaković, Slobodan; Grujić, Jovan; Zeljković, Milan; Blagojević, Zoran; Radojević, Bojan; Popović, Zoran; Živković, Aleksandar; Stevanović, Vladan (Vojnosanitetski pregled, 2014)
Background/Aim. One of the possible complications after implantation of a cement hip-joint endoprosthesis is fracture in the endoprosthesis body. Fractures arise from overload or material fatigue of which an implant is made. The purpose of this research was to define the intensity of maximum stress and the positions of a critical cross-section in the endoprosthesis body. Methods. Unilaterally changing forces which act on the hip joint during walking as well as the loads result in flexible deformations of the endoprosthesis body. Biomechanical analysis of the forces acting on the hip joint determine their direction and intensity, whereas on the basis of Gruen’s classification of the endoprosthesis body loosening the level of fixation is established.  The bodies of cement hip joint endoprosthesis are made of cobalt-chromium-molybdenum (CoCrMo) alloy, suitable for vacuum casting, are submitted to the analysis. Analysis of the critical stress in the endoprosthesis body was performed on the endoprosthesis body by means of the finite element method. The experimental verification of the obtained results was carried out on the physical prototype under laboratory conditions. Results. Computer analysis, by means of the finite element method, determined the stress state by calculation of the maximum Von Mises stress and critical cross-sections for different angles of the resultant force action. The results obtained by the computer and experimental method correlate and are comparable to the results of similar analyses conducted on various endoprosthesis types. Conclusion. The analyses described in the paper make the basis for improving the process designing of hip joint endoprostheses and their customization to each individual patient (custom made).
Keywords: arthroplasty; replacement; hip; fractures; stress; computer simulation